Da intolerância religiosa ao racismo religioso: desafios e possibilidades na sala de aula - Rodrigues, Uliania Marinho (2021)
This dissertation aims to analyze the phenomenon of religious intolerance from the academic production on the subject, published in the form of theses and dissertations, as well as the researcher's incursion into terreiros in the city of Bambuí-MG. She intended to show that the expression 'religious intolerance' does not account for all the processes of violence and persecution that people initiated in religions of African origin go through. In a social context in which it is possible to perceive the re-updating of the colonial structure, theoretical bases were sought that would allow us to affirm that racism is the main element that contributes to the exclusion of religions of African origins and to the discrimination of their adherents. In the search to launch an educational proposal that transgresses the education model that is still permeated by a Christian logic, we found an assertive possibility in the Pedagogy of the Crossroads in favor of the fight against religious racism in the school space. As a theoretical contribution, studies by authors who are affiliated with research on religious racism at school, such as Sidnei Nogueira and Patrício Carneiro, were used. Considering the aspects of carrying out a bibliographic research, the database of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES) was chosen as a database for consultation, using the following descriptors: religious intolerance, school and religious racism. Five works were selected, one thesis and four dissertations, defended from 2015 to 2019. As a result, a chapter on religious intolerance was presented in academic productions, and a discussion on religious intolerance was woven from the works of reference, being identified and listed the proposals to combat the phenomenon, according to the analyzed authors. In addition, the researcher's incursion into the terreiros of the city of Bambuí-MG and her view on the possibilities of practice of combating religious racism through the didactics of the Pedagogy of the Crossroads were shown. The results allowed us to infer that racism is the main element that contributes to the exclusion of African-based religions and their adherents at school, and that some other factors support the process of religious racism in this environment: Eurocentric-Christian ideals, that are still very strong within these spaces; the lack of knowledge about African-based religions on the part of the school community; the colonization of knowledge; the training of education professionals in universities; the lack of continuing education focused on this theme, which should be offered to basic education teachers; and hinders the applicability of Law 10.639/03 (to include in the official curriculum of the Education Network the compulsory theme of Afro-Brazilian History and Culture) in schools.